KEPALA SEKOLAH SEBAGAI PEMIMPIN PERUBAHAN DI SEKOLAH MENENGAH KEJURUAN UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Sri Murwantini (Jurnal Taman Vokasi, 2017)
Principals as managers in schools, especially in vocational schools, face the challenge of changing the implementation of the 2013 curriculum. Preparedness is to recognize elements of change with open attitude, increase knowledge and skills in order to manage change so that schools become adaptive to change. This fundamental change in the 2013 curriculum is known as the element of change, which includes the Graduate Competency Standards, Content Standards, Process Standards and Assessment Standards. As the leader of change, the headmaster of SMK has a concern for the improvement of his "followers" performance and develops his potential followers to reach the highest potential. For that the headmaster of SMK in leading the change must have the characteristics: can be an example, inspiring, stimulating to creative, and pay attention to individual needs of its followers. Through its role as a change leader, the headmaster of SMK gradually builds awareness of urgency to change, mobilizes TPS, develops vision and strategies that reflect the implementation of the 2013 curriculum, communicates the vision continuously, empowers the citizens of schools for the implementation of the 2013 curriculum, generates short-term success, consolidate, and develop a school culture that supports the implementation of the 2013 curriculum.